Project Management and Administration of Financial Assistance to Host Communities of Batangas Power Plants - Binag, Noel Hugo (Social Sciences and Development Review, 2020)
The financial assistance under the Energy Regulations No. 1-94, as amended, of the Department of Energy (DOE) was created to further support the host local government units (LGUs)/regions over and above the various taxes received from the utilization and development of the national wealth within their respective areas as provided under Section 289-294 of the Local Government Code by the LGUs. Moreover, this provision is to secure the endorsements of the host LGUs/regions for the implementation of power projects in their area and in the long run will promote harmony and cooperation among host communities and people affected. The study is focused on evaluation of the financial assistance contributed by independent/private power producers in which energy generation facilities and/or energy resources are located in the province of Batangas, allocated among the social development programs, namely: Electrification Fund (EF); Development and Livelihood Fund (DLF); Reforestation, Watershed Management, Health and/or Environment Enhancement Fund (RWMHEEF). The descriptive-normative research design was used in this study.